Association between Dental Erosion and Diet in Brazilian Adolescents Aged from 15 to 19: A Population-Based Study - Yêska Paola Costa Aguiar; Fábio Gomes dos Santos; Eline Freitas de Farias Moura; Fernanda Clotilde Mariz da Costa; Sheyla Marcia Auad; Saul Martins de Paiva; Alessandro Leite Cavalcanti (The Scientific World Journal)
Dental erosion is a pathological condition resulting from the irreversible dissolution of the mineralized portion of the teeth, being recognized in modern society as an important cause of loss of tooth structure. The aim of this study was to assess the prevalence and its association with diet in Brazilian adolescents of Campina Grande, PB, Brazil. A population-based study was conducted on a stratified sample of 675 adolescents aged from 15 to 19 of both sexes using the index proposed by O'Sullivan. Dental examinations were performed by two calibrated dentists (kappa = 0.82). The significance level adopted was 5%. The prevalence of dental erosion was 21%, and the upper central incisors and lateral incisors were the most affected elements, with 50.5% and 40.2%, respectively. The buccal surface showed greater impairment (51.4%) and 67.8% of teeth with dental erosion had more than half of the surface of affected area. Most damage was on the enamel (93.5%). There were no statistically significant differences between the occurrence of dental erosion and gender, age, socioeconomic status, self-reported ethnicity, and diet. There was high prevalence of dental erosion in its early stages among adolescents and there were no significant differences in the frequency of the consumption of foods and beverages and the presence of dental erosion.